CORPORATE ACTION RESULT (STOCK BUYBACK) TO STOCK PRICE : A STUDY OF BUYBACK AT THE INDONESIA STOCK EXCHANGE IN THE YEAR OF 2014 - 2019 - NANANG SURYANA; SURTIKANTI SURTIKANTI (CV KULTURA DIGITAL MEDIA, 2020)
This research aims to determine the difference in the capital structure and stock price before and after the corporate action (stock buyback), knowing the effect of corporate action to influence the capital structure (Debt to Equity Ratio) to stock price of listed companies on the Indonesia Stock Exchange that conduct corporate action (stock buybacks). The method used in this study is descriptive and verifiative analysis. The analysis method uses simple linear regression. The population in this study was 40 financial statements from various sectors that carried out stock buybacks and were listed on the Stock Exchange for 4 years (2014-2019). The sampling technique usied purposive sampling method with certain criteria, resulting in a sample of 30 financial statements (2014-2019). The hypothetical test results in this study show that (1) The average stock price and capital structure 20 days before and after stock buyback is different, (2) The capital structure (DER before buyback) has a significant influence on stock price of companies listed on the Indonesia Stock Exchange (IDX) that perform corporate action (stock buybacks), but the capital structure (DER after buyback) does not have a significant effect on the stock price of companies that perform corporate actions (stock buybacks).